Cresta Plastic Company a methods study - Chua, Margaret; Mancao, Ma. Ida; Navarro, Marisa; Quiason, Ma. Corazon (College of Engineering, 1986)
This study will cover Cresta Plastic Company's main product- bags. The body of the bag is basically made up of vinyl plastic and a few of its materials include zipper, rivets and thread. The group has narrowed down the type of bag to the most common type of dimension. 12" and 15". This type of bag covers practically the whole operation of the company without being unncessarily too broad in scope. The study analyzes every step of the process, its advantages, likewise, its disadvantages and tries to give a better solution, if there is any. Otherwise, the present situation is maintained. The group's final decisions are guided accordingly by criteria which were formulated and ranked. The group also takes into account factors such as the present plant lay-out, process, material handling, work distribution and flow process.